Indoor positioning system - Khee, Chun Seng (2024)
This project aims to develop an indoor infrared-based positioning system utilizing a low-cost infrared transmitter and infrared receiver. Current IPS solutions suffer from imperfections and vulnerabilities, impacting their effectiveness. Issues such as inaccurate room-level positioning, radio frequency interference, and high development costs can lead to applications relying on IPS techniques providing inaccurate information to users. The primary objective of this project is to create an affordable infrared IPS capable of providing room-level accuracy and overcoming interference issues prevalent in radio-based systems. The novelty of this project lies in the use of infrared technology as the transmitted signal, emphasizing its line-of-sight characteristic, which is often considered a drawback by other systems. Additionally, the low power consumption of infrared supports the scalability and sustainability of this proposed solution, as it does not require frequent changes. The contribution of this research lies in its potential to revolutionize indoor positioning by minimizing infrastructure dependencies, mitigating interference, and offering a globally implementable solution. In terms of impact and significance, the proposed infrared IPS is positioned as a transformative solution, akin to the ubiquity of GPS. By harnessing infrared light and avoiding reliance on radio waves, the system addresses interference issues and reduces development costs, making it accessible for diverse applications.